Simultaneous removal of phosphates and dyes by Al-doped iron oxide decorated MgAl layered double hydroxide nanoflakes. Issue 8 (5th July 2019) - Cheng, Shu; Shao, Luhua; Ma, Jianhong; Xia, Xinnian; Liu, Yutang; Yang, Zhenfei; Yang, Cong; Li, Sijian
Abstract : Study of the adsorption of phosphates, CR and MO in various systems by Al-doped iron oxide decorated MgAl layered double hydroxide nanoflakes. Abstract : Phosphates and dyes commonly coexist in industrial effluents, resulting in serious problems to the environment. Herein, a novel Al-doped iron oxide decorated layered double hydroxide nanocomposite (Al-Fe2 O3 /LDH) was synthesized by a one-step hydrothermal method. The presence of layered hydroxide nanoflakes as a matrix could mediate the growth of oxide nanoparticles. In individual systems, the 1Al-Fe2 O3 /LDH had high adsorption capacities of 93.06 mg P per g, 1363.54 mg g −1 and 577.42 mg g −1 for phosphates, Congo red (CR) and methyl orange (MO), respectively. Adsorption capacities could be mostly achieved in the first minute. The good dispersion of 1Al-Fe2 O3 /LDH and the synergistic effect between layered hydroxide nanoflakes and supported Al-doped iron oxides contributed to the fast and enhanced removal ability. The limited number of reactive sites on the surface of 1Al-Fe2 O3 /LDH had a greater effect on phosphate removal in the phosphate–CR system while the reactive sites had less effect on phosphate removal in the phosphate–MO system, which could be attributed to the differences in the interactions between the adsorbates and the active sites of 1Al-Fe2 O3 /LDH. Moreover, the special affinity for phosphates rather than dyes caused by the Al doping in iron oxides contributed to the enhanced competitive adsorption for phosphates. In addition, the adsorbent powder could be separated after adsorption through natural settling. We proposed that the effective removal of phosphates could be attributed to inner-sphere formation through ligand exchange, electrostatic interaction and hydrogen-bond formation.